A surface charge dependent enhanced Th1 antigen-specific immune response in lymph nodes by transfersome-based nanovaccine-loaded dissolving microneedle-assisted transdermal immunization. Issue 31 (19th July 2019) - Wu, Xuanjin; Li, Yang; Chen, Xiguang; Zhou, Zhongzheng; Pang, Jianhui; Luo, Xin; Kong, Ming
Abstract : The efficient delivery of vaccines to draining lymph nodes and the induction of robust local immune responses are crucial for immunotherapy. Abstract : The efficient delivery of vaccines to draining lymph nodes and the induction of robust local immune responses are crucial for immunotherapy. Transdermal administration has been evidenced to facilitate the delivery of ingredients to lymph nodes. In this study, transfersomes with opposite surface charges were applied for antigen encapsulation and these were integrated with dissolving microneedles to investigate their effects on immune responses via transdermal immunization. The microneedles were easily inserted into mouse skin and achieved the local release of nanovaccines into the dermis through dissolution. Although anionic nanovaccines promoted cellular uptake via DC2.4, cationic nanovaccines exhibited stronger escape capacities from endocytic compartments, facilitating antigen processing via an MHC-I presentation pathway, and formed larger accumulations in lymph nodes. Compared with their anionic counterparts, the cationic nanovaccines more efficiently activated DC maturation and induced Th1 immunity; this was suggested by the significantly increased IgG2a/IgG1 ratio and elevated cytokine secretion from Th1 cells, without an enhancement in the Th2 response. Such an enhanced Th1 antigen-specific immune response in lymph nodes via a transdermal vaccine delivery platform is beneficial for potential immunotherapy approaches.